Vascular access simplified - Davies, Alun H.; Gibbons, Christopher P. (Tfm Pub., 2007)
The need for dialysis access surgery is growing rapidly as the population of patients with end stage renal failure expands. This book is aimed at those healthcare professionals involved in the care of patients undergoing dialysis. It gives a comprehensive review of aspects of adult dialysis access with a specific emphasis on haemodialysis.